2015
DOI: 10.1039/c4fd00249k
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on nanostructure and mechanical properties of single-nanoparticle thick membranes

Abstract: The properties of mechanically stable single-nanoparticle (NP)-thick membranes have largely been studied at room temperature. How these membranes soften as nanoparticle ligands disorder with increasing temperature is unknown. Molecular dynamics simulations are used to probe the temperature dependence of the mechanical and nanostructural properties of nanoparticle membranes made of 6 nm diameter Au nanoparticles coated with dodecanethiol ligands and terminated with either methyl (CH3) or carboxyl (COOH) termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 46 publications
2
23
1
Order By: Relevance
“…MD simulation of two-dimensional non-cross-linked GNP thin film have been carried out by Grest et al [25][26][27]. The single-NP-thick film with alkanethiol-coated GNP has been studied with mechanical test to reveal the mechanical properties, ligand structure, and end group interactions of the NP thin film.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulation of two-dimensional non-cross-linked GNP thin film have been carried out by Grest et al [25][26][27]. The single-NP-thick film with alkanethiol-coated GNP has been studied with mechanical test to reveal the mechanical properties, ligand structure, and end group interactions of the NP thin film.…”
Section: Introductionmentioning
confidence: 99%
“…These dry temperatureannealed samples were then equilibrated for more than 10 ns for comparison with dry samples that were not annealed. We characterize the properties of dry membranes at elevated temperatures elsewhere [49].…”
Section: Methodsmentioning
confidence: 99%
“…Also of interest is the effect of thermal annealing on q ij . We detail elsewhere the weakening of ligand end group and ligand backbone structure with increased temperature [49]. Here we compare ligand end-group and backbone structure before and after thermal annealing.…”
Section: F Ligand Structure Equilibration and Stabilitymentioning
confidence: 99%
“…Molecular dynamics simulation indicated that the single particle thick membrane expanded and ligands unbundled from each other when temperature rised. [122] Experimental results also suggested that the temperature at which the assembly was fabricated could impact on both the film morphology and the temperature-elastic modulus. [125] Membranes that were fabricated at a temperature higher than the phase transition temperature showed a higher degree of interdigitation but were also accompanied with more defects.…”
Section: The Effect Of Temperaturementioning
confidence: 99%
“…In another dynamic simulation, the terminal group of the ligand was found to have a great impact on the mechanical properties of a single-nanoparticle-thick membrane. [121][122] For an assembly with methyl (-CH 3 ) terminated ligands, the interaction among carbon chains and partial interpenetration among ligands were prevailing. However, for a carboxyl (-COOH) terminated ligands system, end-to-end orientations and electrostatic interactions between charges in the COOH groups were the dominant interactions.…”
Section: Short Molecular Ligand Interdigitationmentioning
confidence: 99%